Pyrasulfotole & bromoxynil response in grain sorghum. - Lally, Nathan Gerard (Kansas State University, 2011)
Postemergent herbicide options for grain sorghum are limited and increasingly challenged by the development of herbicide resistant weeds. The herbicide pyrasulfotole & bromoxynil (P&B) was evaluated for potential use in grain sorghum and for control of a suspected HPPD-resistant Palmer amaranth population. Field experiments were conducted near Manhattan and Rossville, KS, to evaluate grain sorghum response to P&B with and without 2,4-D applied to growth stages from 1-leaf through the flag leaf stage and tankmixed with 2,4-D ester, amine, or dicamba applied to 3- and 6-leaf sorghum. The addition of 2,4-D ester did not reduce sorghum injury from P&B alone. Increasing the rate of P&B increased injury. Treatments applied to 1- and 4-leaf sorghum were injured the most. All P&B treated sorghum, regardless of timing, yielded 8 to 20% less than the untreated check. Pyrasulfotole & bromoxynil applied alone or with dicamba injured sorghum less than 2,4-D applied at 3- or 6-leaf. Increasing the rate from 140 to 280 g ha[superscript]-1 2,4-D amine or ester increased injury by 6 to 11%. Yields were lowest when P&B was applied with 2,4-D amine at 140 g ha[superscript]-1 and 2,4-D amine or ester at 280 g ha[superscript]-1 compared to all other treatments. Increasing the rate of growth regulator herbicides decreased yields by 8% and did not reduce crop injury from P&B alone. Greenhouse and field experiments were conducted to evaluate the response of two suspected P&B-resistant (R1 & R2) and one susceptible (S) Palmer amaranth population to P&B, atrazine, and tembotrione. Herbicides were applied when plants were 7 to 19 cm tall. The S population was controlled with less than field use rates. A resistance index (RI) of 4.8 to 11.0 was determined for R1 and R2 in greenhouse and field experiments. Tembotrione controlled 100% of S in all experiments, while providing 63 to 86% injury to R1 and R2 populations. Atrazine did not control the resistant populations. Pyrasofotole & bromoxynil will be an valuable tool for weed control in sorghum, however, Palmer amaranth populations exist that will not be controlled.
Keywords: Pyrasulfotole & bromoxynil; HPPD inhibitors; Palmer amaranth; Grain sorghum; Agronomy (0285)